2014
DOI: 10.12659/msm.892130
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant Methylation of CDH13 is a Potential Biomarker for Predicting the Recurrence and Progression of Non Muscle Invasive Bladder Cancer

Abstract: BackgroundCDH13 is a novel tumor suppressor gene often inactivated by aberrant promoter methylation in human cancers. Previous studies have shown that CDH13 methylation correlated with advanced disease and poor prognosis in non-muscle invasive bladder cancer (NMIBC). The aim of the current study was to investigate the correlations between CDH13 methylation and disease recurrence as well as progression of NMIBC.Material/MethodsThe methylation status of CDH13 in 178 NMIBC samples and 38 normal bladder epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…SNCG has been reported to have a strong connection with malignancies such as breast, gastric, pancreatic, esophagus, colon, and prostate cancers [ 13 18 ]. Many genes, including SNCG, are involved in DNA methylation, which plays an important role in the occurrence and development of tumors [ 19 21 ]. Furthermore, SNCG is also involved in resistance to certain chemotherapeutic or antimicrotubule agents in breast cancer treatment [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…SNCG has been reported to have a strong connection with malignancies such as breast, gastric, pancreatic, esophagus, colon, and prostate cancers [ 13 18 ]. Many genes, including SNCG, are involved in DNA methylation, which plays an important role in the occurrence and development of tumors [ 19 21 ]. Furthermore, SNCG is also involved in resistance to certain chemotherapeutic or antimicrotubule agents in breast cancer treatment [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Surgical resection is still the most effective therapy for non-invasive TCC patients. Although chemotherapy based on BCG may reduce recurrence in patients, approximately 70% will recur and 25±30% will eventually progress to muscle invasive disease or distant metastasis [ 4 , 5 ]. Thus, there is an urgent need to find new therapeutic targets and strategies, which may be helpful in understanding the molecular mechanisms and improving TCC therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Finally, all of the Portuguese studies were conducted by Dr. Carmen Jerónimo's group in IPO (Portuguese Oncology Institute) [32][33][34][35][36]. Regarding Asian studies, significant contributions have been made by Dr. Ying-Li Lin [37][38][39][40][41][42][43] at Jiangsu University and Dr. Liqun Zhou (especially in UTUC studies) [44][45][46]…”
Section: Resultsmentioning
confidence: 99%
“…The studies by Dr. Lin at JU have reported that methylation of CDH13 is associated with increased recurrence risk (p=0.0043), shorter time to progression (p=0.006), lower RFS (p<0.0001) [43] and with an increased risk of death (p=0.0071) [41]. In another of his studies, CDH11 methylation correlated with poor OS (p=0.0004) [40].…”
Section: Cell-adhesionmentioning
confidence: 96%